A study of indoor environmental factors in University offices on Malaysia's East Coast to enhance well-being - Darliana Mohamad; Ahmad Farhan Shauki Sulong; Nurdini Mohammad Shukri; Siti Sarah Abdul Basir; Norhidayu Noruddin; Mohd Khalid Ab Kadir@Musa (Universiti Kebangsaan Malaysia, 2025)
This study investigates indoor environmental factors in several offices from one of the university at Malaysia's East Coast, focusing on enhancing occupational health and well-being among university staff by examining lighting quality and thermal comfort. Monitoring sampling were done based on hazard reports logged and data from three main offices or location were collected in this study. Utilizing Extech HD450 Heavy Duty Data Logging Light Meter to measure illuminance, the study found that most sampled points fell below the Occupational Safety and Health Guidelines' recommended range of 300-500 lux, indicating insufficient lighting that can cause visual discomfort and reduce productivity. Thermal comfort assessments, conducted with EVM-7 Indoor Air Quality 3M QUEST and AirPro Solution Models AP500, revealed acceptable temperature and humidity levels but often inadequate air velocity, particularly in the Science Officer's Office, leading to poor air circulation and potential health issues. The study highlights the necessity of improving lighting solutions by installing additional fixtures or upgrading existing ones for sufficient and evenly distributed illumination and enhancing ventilation systems to ensure adequate air movement. Addressing these deficiencies is crucial for creating a conducive working environment, promoting employee satisfaction and productivity. This research focuses solely on monitoring and analyzing the collected data. No qualitative evaluation has been conducted as part of this study. This research advocates for a holistic approach to Indoor Environmental Quality (IEQ), involving regular assessment and targeted interventions to enhance the overall quality of university office environments, ultimately fostering a healthier and more productive workplace.